Posterior Reversible Encephalopathy Syndrome (PRES) with Hypertensive Retinopathy and Hyperaldosteronism - Nagpal, Chand; Mesiano, Taufik; Rasyid, Al; Hidayat, Rakhmad; Pangeran, David; Kurniawan, Mohammad; Harris, Salim (Acta Neurologica Indonesia, 2026)
Introduction: Posterior Reversible Encephalopathy Syndrome (PRES) is a neurological syndrome with an acute or subacute onset characterized by reversible cerebrovascular dysregulation. Hypertension is the primary risk factor for PRES, however other conditions such as hyperaldosteronism accompany and precipitate PRES. Case Report: This case illustrates a 32-year-old man without prior medical history with loss of consciousness and seizures 1 day prior to admission with blurry vision and vomiting 2 weeks prior that progressed gradually. Brain MRI revealed vasogenic edema of bilateral occipital lobes. The patient was assessed for hypertensive retinopathy and suspected primary hyperaldosteronism. Management with anti-hypertensives, anti-epileptic medications, electrolyte correction and supportive therapy was given, and the patient improved gradually and was discharged 10 days later without any complications. Discussion: No diagnostic criteria is available for PRES, however brain MRI is the crucial to establish a diagnosis of PRES. The resolution of symptoms with blood pressure regulation is another validation of the diagnosis of PRES. Ruling out differentials is prudent to ensure appropriate therapy. Management of PRES encompasses blood pressure regulation, anti-epileptic medications, treating other causes such as drug exposure and metabolic disorders. Previous reports PRES due to secondary hypertension attributed to primary hyperaldosteronism have been reported, although evidence about this causality is limited, nonetheless must be explored and treated as a cause of the hypertension triggering PRES. Conclusion : PRES is a neurological syndrome that is reversible, with hypertension as the primary risk factor that could be secondary due to disorders like primary hyperaldosteronism, that could ultimately trigger PRES.